Comparison of Post Operative Early Active and Passive Mobilization of Flexor Tendon in Zone 2 - Fereydoun Layeghi; Maryam Farzad (Iranian Rehabilitation Journal, 2012)
Objectives: Despite numerous studies, having the best outcome is challenging after flexor tendon repairs in zone 2. This study were done to test the hypothesis that immediate postoperative active mobilization will achieve similar outcomes to passive mobilization.